The warning - Patterson, James, 1947-; Wells, Robison E (Grand Central Publishing, 2019)
Returning home after a power-plant accident, Maggie and Jordan discover something is very wrong and as friends and family morph into terrifying strangers, their search for the truth puts them in the crosshairs of a sinister presence.